Combining theoretical concepts and tools: mapping human deprivation in the City of Cape Town - Fontaine, Danielle (Department of Environmental and Geographical Science, 2024)
[missing pages: 60,77,80,91] Human deprivation represents a contemporary 'paradox of development' that urgently nee4J to be addressed at the city scale. This research explores the argument that confusion over the measurement of human deprivation still exists, despite various development initiatives, in part because of a disconnect between contemporary development discourse and the research tools used to identify and investigate the poor. Development discourse defines human deprivation according to elements of difference, diversity and the dynamic nature of human needs; research tools identify and investigate human needs based on homogeneity, similarity and a fixed status quo. To explore the implications of this disconnect for human deprivation at the city scale, three concepts namely, poverty, chronic poverty and vulnerability, and the practical tools of socio-economic indicators and geographical information systems (GIS) are interrogated and critiqued for their usefulness for mapping human deprivation at the city scale. Poverty, chronic poverty, and vulnerability are three integral concepts of the Millennium Development Goals (MDGs); they highlight different aspects of deprivation including, amongst others, multiple dimensions, temporality and change, and biophysical risk, respectively. Socio-economic indicators and GIS are tools currently used by various disciplines, research institutions and levels of government in an array of research and practical applications. Socio-economic indicators are a method of converting qualitative data into quantitative data, and GIS can be used to translate these quantitative data into visual representations, thereby revealing spatial distributions. Socio-economic indicators hence provide the ''link" between the theoretical and the visual. Socio-economic indicators and GIS are useful, and in the case of GIS, contingent tools, but do have limitations to their application at the city scale that originate from the availability of appropriate data.